Global landform and lithology class at 250 m based on the USGS global ecosystem map - Tomislav Hengl (Zenodo, 2018)
Layers include: lithology (15) and landform (7) indicator maps (0-100%). Derived from the USGS Global Ecosystem Map ,i.e. the EcoTapestry map. Water bodies masked out. Antarctica is not included. To access and visualize maps use: OpenLandMap.org If you discover a bug, artifact or inconsistency in the maps, or if you have a question please use some of the following channels: Technical issues and questions about the code: https://gitlab.com/openlandmap/global-layers/issues General questions and comments: https://disqus.com/home/forums/landgis/ All files internally compressed using "COMPRESS=DEFLATE" creationoption in GDAL. File naming convention: dtm = theme: digital terrain models / relief and soil, lithology = variable: lithological class, usgs.ecotapestry = determination method: USGS Global Ecosystem Map, p = probability 0-100%, 250m = spatial resolution / block support: 1 km, s0.0cm = vertical reference: land surface, 2014 = time reference: year 2014, v1.0 = version number: 1.0